Is Central Europe Safe from Environmental Lead Intoxications? A Case Series - Pelclová, Daniela; Šťastná, Jana; Vlčková, Štěpánka; Vlček, Kamil; Urban, Michal; Laštovková, Andrea; Doležel, Zdeněk (Central European journal of public health, 2016)
Preventive measures in Central Europe were successful in suppressing both occupational and environmental lead exposure so that they did not constitute a severe public health problem. However, rare lead intoxications still appear. We report on lead intoxication in four family members where the source was removed lead ceiling paint. The symptoms of the lead intoxication started several weeks after removal and the inhalational exposure to the minimum dust residues lasted for more than three months before the poisoning was diagnosed. Father developed anaemia and saturnine colics. He and his two daughters received antidotal treatment which had to be repeated in the children. Finally, all recovered completely.Lead intoxication may be easily overlooked due to the unspecific symptoms. It is necessary to think of this rare poisoning which may be caused by old paints, historical ceramics and lead shots, in addition to commercial products imported from abroad.
Keywords: psi; Infant; Humans; Dogs; kojenec; nátěrové hmoty; prevention; Paint; Female; vystavení vlivu životního prostředí; dospělí; Housing; lidé; zvířata; treatment; lead; předškolní dítě; Adult; bydlení; ženské pohlaví; Male; intoxication; Lead Poisoning; Czech Republic; Environmental Exposure; Animals; Česká republika; mužské pohlaví; Child, Preschool; paints; diagnosis; otrava olovem